Dataset for Xia et al.: Reproductive isolation via divergent genital morphology due to cascade reinforcement in Ohomopterus ground beetles - Takami, Yasuoki (Dryad, 2022)
Secondary contact between incipient species and selection against
maladaptive hybridization can drive reinforcement between populations in
contact and result in reproductive character displacement (RCD). Resultant
divergence in mating traits within a species may generate downstream
reproductive isolation between populations with displaced and
non-displaced traits, referred to as the cascade reinforcement hypothesis.
We examined this hypothesis using three allopatric populations of the
ground beetle Carabus maiyasanus with a genital
lock-and-key system. This species shows RCD in male and female genital
morphologies in populations in contact with the sister species C.
iwawakianus. In a reciprocal mating experiment using three allopatric
populations with differences in male and female genital sizes,
inseminationfailure increased as the difference in genital size increased.
Based on the reproductive isolation index, insemination failure was the
major postmating-prezygotic isolation barrier, at least in one population
pair with comparable total isolation to those of other species pairs. By
contrast, there was only incomplete premating isolation among
populations. These results suggest that RCD in genital
morphologies drives incipient allopatric speciation, supporting the
cascade reinforcement hypothesis. These findings provide insight into the
roles of interspecific interactions and subsequent trait diversification
in speciation processes.
Keywords: FOS: Biological sciences